Template-free synthesis of boron nitride foam-like porous monoliths and their high-end applications in water purification. Issue 4 (12th January 2016) - Xue, Yanming; Dai, Pengcheng; Jiang, Xiangfen; Wang, Xuebin; Zhang, Chao; Tang, Daiming; Weng, Qunhong; Wang, Xi; Pakdel, Amir; Tang, Chengchun; Bando, Yoshio; Golberg, Dmitri
Abstract : New boron nitride porous monoliths with high efficiency and excellent adsorption applications were successfully fabricated by a brand-new and template-free method. Abstract : It has remained a great difficulty and challenge to prepare BN-based porous monoliths (BNPMs) via a facile method. Here, we report a brand-new and high-throughput synthesis of BNPMs through a facile two-step template-free reaction including self-bubbling precursor solidification and high-temperature pyrolysis. The resulting BNPMs with an interconnected open-bubble structure exhibit the highest specific surface area ever reported for the BNPM systems, up to 1406 m 2 g −1, and high bulk crush strength of ∼1 MPa. Thanks to the spacious hydrophobic surfaces of the BNPM system, the material was applied for the highly efficient separation–adsorption purification of an oil/water system, demonstrating an excellent adsorption capacity of up to 71–98% (volume-based adsorption capacity) toward a wide selection of oil contaminants. Besides, the present BNPMs were designed as a filtration column which rapidly removed rhodamine B (RB) and Cd(ii ) pollutants from an aqueous solution under a forced filtration–adsorption process, corresponding to an ultrahigh removal capacity of 554 mg g −1 and 561 mg g −1, respectively. Thus, the obtained BNPMs are envisaged to become a fairly promising adsorbent for water cleaning.